2021
DOI: 10.3389/fonc.2021.631007
|View full text |Cite
|
Sign up to set email alerts
|

Non-Genomic Actions of Estrogens on the DNA Repair Pathways Are Associated With Chemotherapy Resistance in Breast Cancer

Abstract: Estrogens have been implicated in the etiology of breast cancer for a long time. It has been stated that long-term exposure to estrogens is associated with a higher incidence of breast cancer, since estradiol (E2) stimulates breast cell growth; however, its effect on DNA damage/repair is only starting to be investigated. Recent studies have documented that estrogens are able to modify the DNA damage response (DDR) and DNA repair mechanisms. On the other hand, it has been proposed that DDR machinery can be alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Estrogen signaling pathway is one of the most important pathways involved in steroid hormones and reproductive regulation in mammals ( Saito and Cui, 2018 ), and estrogens are also associated with tumor development, particularly breast and ovary cancers ( Ferreira et al, 2009 ). Studies also demonstrated that estrogen is also related to the DNA repair pathways and DNA integrity ( Jiménez-Salazar et al, 2021 ; Pescatori et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen signaling pathway is one of the most important pathways involved in steroid hormones and reproductive regulation in mammals ( Saito and Cui, 2018 ), and estrogens are also associated with tumor development, particularly breast and ovary cancers ( Ferreira et al, 2009 ). Studies also demonstrated that estrogen is also related to the DNA repair pathways and DNA integrity ( Jiménez-Salazar et al, 2021 ; Pescatori et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the key role of this receptor in the growth and survival of hormone-dependent cancer cells, ERα constitutes an important diagnostic and therapeutic target. ERα thus regulates the transcription of many genes involved in cell proliferation through genomic and nongenomic actions [ 151 , 152 , 153 , 154 , 155 ]. While the classical genomic effects are better established, the impact of the non-genomic plasma membrane receptor pathway as well as the rapid stimulation of intracellular signaling cascades are still under active investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In HR+ tumors we mainly observed resistance patterns in PI3K/Akt pathways, regulation of MAPK cascade, ECM-related pathways, lipid transport and ABC transporters pathways. Indeed, Non-genomic activity of estrogens has been suggested to induce chemoresistance, activating PI3K/AKT and modifying DNA damage response [43]. Resistance patterns emerged in specific subsets of ABC transporters, the ABCA2 family, involved in steroid transport that may regulate breast cancer proliferation and survival, as was suggested in a prostate cancer study [46].…”
Section: Discussionmentioning
confidence: 99%